Perlakuan Agens Hayati untuk Mengendalikan Hawar Daun Bakteri dan Meningkatkan Produksi Benih Padi Sehat - Zamzami, Ahmad; Ilyas, Satriyas; Machmud, Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe research objectives were to evaluate biological agent treatments in controlling bacterial leaf blight (BLB) and increasing plant growth and seed production of rice. The experiment was conducted in the greenhouse and field using the same experimental design (randomized block design with two factors) and three replications. The first factor was seed treatments, i.e. negative control, positive control, streptomycin sulphate 0.2%, Pseudomonas diminuta + Bacillus subtilis, matriconditioning + streptomycin sulphate 0.2%, and matriconditioning + P. diminuta + B. subtilis. Spraying plants (second factor): untreated control, streptomycin sulphate 0.2%, biological agent F112, biological agent F198, and biological agent F57. In the greenhouse, matriconditioning + P. diminuta + B. subtilis improved seed germination, plant height, and plant dry weight. Spraying plants with biological agent F112 increased plant dry weight. Meanwhile, matriconditioning + P. diminuta + B. subtilis followed by spraying plants with biological agent F112 reduced the BLB severity. In the field, matriconditioning + P. diminuta + B. subtilis improved seedling dry weight. Matriconditioning + P. diminuta + B. subtilis and spraying plants with biological agents F112 controlled BLB and increased plant growth. However, all treatments were not able to increase healthy seed production.Keywords: matriconditioning, seed treatment, phyllosphere biological agents, Xanthomonas oryzae pv. oryzae